From Underestimated to The Most Respected: The Transformation Steps - Siahaan, Andriyuda; Ratnawati, Kusuma; Susilowati, Christin (Jurnal Aplikasi Manajemen, 2024)
This study focuses on spare part management within the context of a maintenance service company, with a case study on one of the largest State-Owned Enterprise (SOE) subsidiaries in Indonesia engaged in port maintenance services. Spare part management has unique characteristics that distinguish it from other inventory management types, such as irregular demand patterns, a wide variety of items, obsolescence risks, and a close connection to maintenance activities. Failure in spare part management can trigger significant operational and financial problems. This research aims to explore the steps taken to improve and assess the effectiveness of these measures. A phenomenological approach was used to deeply and contextually explore the phenomena. Data was analyzed using qualitative methods with the NVivo application. The study results reveal five main gaps in spare part management, including the lack of clear SOPs, ineffective financial control, inconsistency in spare part naming, weaknesses in inventory control, and manual request processes. The transformation undertaken includes the implementation of a centra application, training, and socialization, the establishment of clear business processes, good inventory management, and increased transparency and accountability. These improvement steps have proven effective in enhancing operational efficiency, cost savings, real-time billing, accurate recording and monitoring, effective evaluation, and increased customer satisfaction. This transformation demonstrates the importance of cross-functional collaboration and good management of information flow. This study emphasizes that good spare part management can improve company performance. The novelty of this research lies in its comprehensive analysis of spare part management improvements in a large SOE context and its practical recommendations for optimizing such systems. Enhanced operational performance and strategic insights for other organizations facing similar challenges in spare part management. The study contributes to the literature by exploring the complexities of spare parts management.